Infrared to visible up-conversion emission in Er3+/Yb 3+ codoped fluoro-phosphate glass-ceramics - Ledemi, Yannick; Amraoui, Mohammed El; Ferrari, Jefferson L.; Fortin, Pier-Luc; Ribeiro, Sidney J.L. [UNESP]; Messaddeq, Younes [UNESP] (Wiley, 2013)
Erbium Er3+ and ytterbium Yb3+ codoped fluoro-phosphate glasses belonging to the system NaPO3-YF 3-BaF2-CaF2 have been prepared by the classical melt-quenching technique. Glasses containing up to 10 wt% of erbium and ytterbium fluorides have been obtained and characterized using differential scanning calorimetry (DSC) and UV-visible and near-infrared spectroscopy. Transparent and homogeneous glass-ceramics have been then reproducibly synthetized by appropriate heat treatment above glass transition temperature of a selected parent glass. Structural investigations of the crystallization performed through X-ray diffractometry (XRD) and scanning electron microscopy (SEM) have evidenced the formation of fluorite-type cubic crystals based during the devitrification process. Finally, infrared to visible up-conversion emission upon excitation at 975 nm has been studied on the Er3+ and Yb 3+ codoped glass-ceramics as a function of thermal treatment time. A large enhancement of intensity of the up-conversion emissions-about 150 times- has been observed in the glass-ceramics if compared to the parent glass one, suggesting an incorporation of the rare-earth ions (REI) into the crystalline phase. © 2012 The American Ceramic Society.
Keywords: Crystalline phase; Devitrification process; Infrared-to-visible; Melt quenching techniques; Rare earth ions; Structural investigation; Up-conversion emission; Ytterbium fluorides; Differential scanning calorimetry; Glass ceramics; Heat treatment; Scanning electron microscopy; X ray diffraction analysis; Ytterbium; Erbium